2020
DOI: 10.3390/foods9060829
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant and Anti-Inflammatory Properties of Rice Bran Phenolic Extracts

Abstract: Oxidative stress and inflammation are known to be linked to the development of chronic inflammatory conditions, such as type 2 diabetes and cardiovascular disease. Dietary polyphenols have been demonstrated to contain potent bioactivity against specific inflammatory pathways. Rice bran (RB), a by-product generated during the rice milling process, is normally used in animal feed or discarded due to its rancidity. However, RB is known to be abundant in bioactive polyphenols including phenolic acids. This study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Our result was consistent with previously reported results that gallic acid was mostly evident in the bran fraction of non-pigmented rice [ 19 ]. p -Hydroxybenzoic acid has been reported to be the major phenolic acid in rice husk and cereal grains, such as wheat, barley, and corn [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our result was consistent with previously reported results that gallic acid was mostly evident in the bran fraction of non-pigmented rice [ 19 ]. p -Hydroxybenzoic acid has been reported to be the major phenolic acid in rice husk and cereal grains, such as wheat, barley, and corn [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic acids exhibited higher antioxidant activities than those of α-tocopherol, anthocyanins, and γ-oryzanol [ 19 ]. A recent study has been shown that phenolic compounds of rice bran extract have the potential to reduce oxidizing free radicals and suppress ROS formation in an oxidative stress environment through the inhibition of radical-producing enzymes and the enhancement of an antioxidant defense system [ 30 ]. In addition, hydroxide groups of polysaccharides serve as electron donors and stabilize free radicals, thereby terminating radical chain reactions [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rice bran is a low-priced, underutilized major by-product of rice processing [ 1 ]. Rice bran contains protein (12–16%), fat (15–20%), and fiber (23–28%) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the milling and processing of rice leaves the polished white rice grains depleted of these nutrients, and the bran is commonly used in animal feed or discarded [20,24]. Rice bran has demonstrated a number of health benefits in people across the lifespan, including as a nutrient-dense source of prebiotics and phytochemicals with antioxidant, anti-inflammatory, and chronic disease-fighting properties [25][26][27]. The potential benefits for the prevention of diarrheal disease via microbiome modulation further contribute to healthy guts and microbiomes [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%